Porous Carbon Nanoparticle Networks with Tunable Absorbability - Dai, Wei; Kim, Seong Jin; Seong, Won-Kyeong; Kim, Sang Hoon; Lee, Kwang-Ryeol; Kim, Ho-Young; Moon, Myoung-Woon (NATURE PUBLISHING GROUP, 2013)
Porous carbon materials with high specific surface areas and superhydrophobicity have attracted much research interest due to their potential application in the areas of water filtration, water/oil separation, and oil-spill cleanup. Most reported superhydrophobic porous carbon materials are fabricated by complex processes involving the use of catalysts and high temperatures but with low throughput. Here, we present a facile single-step method for fabricating porous carbon nanoparticle (CNP) networks with selective absorbability for water and oils via the glow discharge of hydrocarbon plasma without a catalyst at room temperature. Porous CNP networks were grown by the continuous deposition of CNPs at a relatively high deposition pressure. By varying the fluorine content, the porous CNP networks exhibited tunable repellence against liquids with various degrees of surface tension. These porous CNP networks could be applied for the separation of not only water/oil mixtures but also mixtures of liquids with different surface tension levels.
Keywords: RECENT PROGRESS; FIELD-EMISSION; SURFACE; WETTABILITY; NANOTUBES; FILMS